Effects of lead pollution on some biochemical and haematic indicators of natives living in tin mine area, Thai Nguyen province - Hong Van, Luong Thi; Hue, Dam Thi; Son Ha, Nong Thai (Academia Journal of Biology, 2014)
In this research, the authors carried out analysing the content of Pb in peripheral blood samples by AAS. The results showed that the content of Pb in blood samples of natives living in the Ha thuong commune, Dai tu district, Thai nguyen province are 5 times higher than those in control (p < 0.05). There is a change in some biochemical and hematology indicators, such as:  The activity of SGOT in blood of natives (group 1) are higher than those in group 2 (p < 0.05); The De Ritis index in group 1 is 1.6 (high) while in group 2 is 1.3 (normal); The number of human who have basoerythrocytes increase in group 1 (p<0.05); The number of human who monocytes increase in group 1 (p < 0.05). There was a correlation (r = 0.4; p < 0.05) between the content of Pb with the activity of SGOT in blood of natives living in the Hathuong commune, Daitu district, Thainguyen province.